The Current and Future Costs of Colorectal Cancer Attributable to Red and Processed Meat Consumption in Brazil - De Moraes-Ferrari, G (BioMed Central Ltd, 2023)
Background: Compelling evidence supports the association between red and processed meat consumption and increased risk of colorectal cancer. Herein, we estimated the current (2018) and future (2030) federal direct healthcare costs of colorectal cancer in the Brazilian Unified Health System attributable to red and processed meat consumption. Considering reduced red and processed meat consumption, we also projected attributable costs of colorectal cancer in 2040. Methods: We retrieved information on red and processed meat consumption from two nationally representative dietary surveys, the Household Budget Survey 2008–2009 and 2017–2018; relative risks for colorectal cancer from a meta-analysis; direct healthcare costs of inpatient and outpatient procedures in adults ≥ 30 years with colorectal cancer (C18-C20) from 2008–2019 by sex. Results: Attributable costs of colorectal cancer were calculated via comparative risk assessment, assuming a 10-year lag. In 2018, US$ 20.6 million (8.4%) of direct healthcare costs of colorectal cancer were attributable to red and processed meat consumption. In 2030, attributable costs will increase to US$ 86.6 million (19.3%). Counterfactual scenarios of reducing red and processed meat consumption in 2030 suggested that US$ 2.2 to 11.9 million and US$ 13 to 74 million could be saved in 2040, respectively. Conclusion: Red and processed meat consumption has an escalating economic impact on the Brazilian Unified Health System. Our findings support interventions and policies focused on primary prevention and cancer. © 2023, The Author(s).